A taxonomic review of the genus Dolichomitus Smith (Hymenoptera: Ichneumonidae: Pimplinae) from South Korea with descriptions of two new species - Choi, Jin-Kyung; Kolarov, Janko; Jeong, Jong-Chul; Lee, Jong-Wook (Zootaxa, 2016)
Nineteen species of the genus Dolichomitus Smith (Hymenoptera: Ichneumonidae: Pimplinae) are recognized from South Korea, including 15 newly recorded species as well as two species new to science, Dolichomitus koreanus sp. nov., and D. rufinus sp. nov., A key to the species of the genus Dolichomitus in South Korea is provided, together with diagnostic illustrations.